Multi-Stakeholder Coordination Practices in Public Services (Study on Civil Registration of Children's Age in Bandar Lampung) - Vincensius Soma Ferrer (Budapest International Research and Critics University, 2022)
This study highlights the need to actualize the multi-stakeholder coordination process in a child civil registration service. The idea of multi-stakeholder coordination in a public service arises from taking one of the essences of the concept of collaborative governance. This research uses a qualitative approach with the locus located in Bandar Lampung City. Coordination-based public services were initiated by the Bandar Lampung Population and Civil Registration Service as an innovation to optimize civil registration for children. The results of this study show that coordinating public service has succeeded in having a good impact on the ownership of population administration at the age of the child. Criticism that the coordination context that needs to be actualized is present after showing that all children in Bandar Lampung have not yet had a population administration document sent as regulated by the Law of the Republic of Indonesia.